Adopsi Teknologi Sistem Cad/Cam Pada Industri Tekstil Dan Garmen - ., Ismail (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
Industry of textile and garment is one of the national priorities, but the industrial growth slowing down, this is due to the condition of an old machine. In industry of textile and garment, techgnology CAD/CAM system is relative new technology and has been provided by the vendors CAD/CAM systems, however the adoption rate is still low. Therefore, it is necessary to measure the extent of the influence from the factors that influence adoption technology CAD/CAM systems. This study aims to identification factors that affect the adoption technology CAD/CAM systems and develop a model CAD/CAM systems adoption. This model was developed from basic models the technology organization environment (TOE) framework and individual context. Ten hypotheses were develop in this study and data processing use method Partial Least Square (PLS) with software Smart PLS 4.0 Survey was conducted using questionnaires, successfully raised as much as 94 respondent from large textile and garment companies. Results of this research are proofing factors positive effect to adoption technology CAD/CAM systems are Relative Advantage, Compability, Complexity, Cost, Top Management Support, Technical Skill, Export Orientation, External Pressure, External Support and CEO’s or CIO’s Knowledge Level.